Paleoenvironment changes during the past 25,000 yr BP recorded from Lake Maudit, northern Madagascar - Vincent Montade; Hermann Behling; Thomas Kasper; Gerhard Daut; Laurent Bremond; Sylvie Rouland (PANGAEA, 2021)
The dataset represents pollen and sedimentary charcoal counting data as well as XRF and grain size data of the lacustrine sediment core recovered from Lake Maudit in Montagne d extquotesingleAmbre (northern Madagascar, 1,250 m asl). From the center of the Lake Maudit, accessible from a peat bog, two parallel sediment cores (LM1A and LM1B) with lengths of 10.50.167emm and 10.750.167emm were recovered in 2017 using a Russian peat corer in June 2017 by Vincent Montade, Laurent Bremond and Sandratrinirainy Ranarilalatiana. For pollen and extraction, 0.5 cm3 subsamples at an interval varying between 8 and 480.167emcm on LM1B were treated with hydrochloric acid, hydrofluoric acid, acetolysis mixture and stored in glycerol. A minimum sum of 300 terrestrial pollen grains was counted for each subsample using a light microscope at 400x magnification. Pollen and fern-spore percentages were calculated on the terrestrial pollen sum. For charcoal-particle extraction, 1 cm3 of sediment was sampled every cm along the core LM1B and soaked in a 3% NaP2O4 solution plus bleach for several hours to deflocculate sediments and oxidize organic matter. Samples were sieved through a 160 μm mesh and charcoal particles were counted using a stereomicroscope at x40 magnification coupled to a digital camera. Semi-quantitative measurements of inorganic chemical elements were conducted using an ITRAX (CS-8) X-Ray fluorescence (XRF) core scanner with a molybdenum (Mo) tube at the Geomorphological–Sedimentological Laboratory of the Geomorphology and Polar Research (GEOPOLAR), University of Bremen. XRF scanning was conducted at 550.167emkV and 300.167emmA with 100.167ems of exposure time at 0.2 mm resolution from both sediment cores, LM1A and LM1B. These elements were normalized to the counts of incoherent radiation (“Mo inc”) derived from the XRF scanner, to account for lithological changes and sediment matrix effects. Using the XRF data, a Principal Component Analysis (PCA) was carried out, using the selected elements (Si, K, Ca, Ti, Mn, Fe, and Ni) as input variables. Prior to this multivariate statistic, the normalized elements were transformed using standard “z-transformation”. The PCA carried out with XRF data resulted in three main axes, with Axis 1 representing 61.5%, Axis 2 24.4%, and Axis 3 9.4% of the total data variance. For the grain size analysis ~1 cm3 subsamples at an interval of 50.167emcm were taken on LM1A and measured after destroying carbonates and organic matter according to standard protocols with HCl and H2O2. Measurements were carried out with a laser diffraction particle-size analyzer (LS 13320 Beckman Coulter) in seven cycles of 600.167ems each. The first reproducible signal was considered as reliable and final distribution data were calculated using the Fraunhofer optical model. Based on the lithological description (marker layers), the XRF-element patterns, and digital and radiographic images, LM1A and LM1B were parallelized and combined to a composite core (depth 1). In addition, several event-related deposits (deposited within only hours or maybe days) originating from the catchment have been identified. These events disturbed the normal sedimentation process and were removed to correct the master core depth (depth 2) before establishing the age-depth model. Between 0 and 208 cm the sediment core corresponds to peat sediment and below 208 cm to lacustrine sediment. Age-depth model have been only established on the lacustrine sediment section.